The economics of platforms : concepts and strategy - Belleflamme, Paul; Peitz, Martin (Cambridge : Cambridge University Press, 2021)
Digital platforms controlled by Alibaba, Alphabet, Amazon, Facebook, Netflix, Tencent and Uber have transformed not only the ways we do business, but also the very nature of people's everyday lives. It is of vital importance that we understand the economic principles governing how these platforms operate. This book explains the driving forces behind any platform business with a focus on network effects. The authors use short case studies and real-world applications to explain key concepts such as how platforms manage network effects and which price and non-price strategies they choose. This self-contained text is the first to offer a systematic and formalized account of what platforms are and how they operate, concisely incorporating path-breaking insights in economics over the last twenty years.
Title from publisher's bibliographic system (viewed on 12 Oct 2021).
Keywords: Multi-sided platform businesses